A Theoretical Proposal for a Perceptually Driven, Food-Based Disgust that Can Influence Food Acceptance During Early Childhood - Brown, Steven Daniel; Harris, Gillian (International Journal of Child Health and Nutrition, 2022)
Disgust, the “revulsion at the prospect of (oral) incorporation of an offensive substance”, is not thought to influence the acceptability of food during infancy and early childhood. This is because the feelings of disgust require a person to have developed an understanding of contagion and to be aware of the nature and origin of a given disgust stimulus, which does not occur until around seven years of age. Despite this need for higher cognitive functioning, studies have demonstrated the potential for disgust in children as young as two years of age. Furthermore, it seems that young children can demonstrate aspects of disgust without having the cognitive understanding of contagion. This review is the first paper to demonstrate how core disgust may influence the acceptability of foods from late infancy. Firstly, food neophobia may act as a catalyst for disgust. Secondly, that disgust in young children can result from the visual perceptual features of food (as opposed to a cognitive response based on non-food disgust stimuli). Thirdly, that some disliked foods have contaminating properties, much like non-food, adult disgust stimuli (e.g. insects). Fourthly, that the response reduces as the child ages and learns more about food and its variability between presentations. Finally, individual differences exist to explain why an individual child may be more or less likely to respond to a given food with a disgust response. This proposal adds to the current debate relating to the motivations of ‘picky’ eating during early childhood and introduces an alternative to the proposal that these behaviours are the result of a child’s desire for autonomy.